Il rapporto tra Archeologia Preventiva e sviluppo Infrastrutturale: Progettare il domani attraverso la storia. L’esperienza del Gruppo Ferrovie dello Stato e di Italferr - Frandi, Francesca (GEOmedia, 2024)
Gruppo Ferrovie dello Stato Italiane, has been the first Italian engineering company to equip itself, since the 1990s, with its own staff of professional archaeologists capable of managing all archaeological activities functional to the design and construction of railway works and to resolve any interference between new railway works and the archaeological heritage. The team works in collaboration with the territorially competent Archaeological Superintendencies in Italy and is registered in the Ministry of Culture’s list of operators qualified to draw up the Archaeological Assessment Document, bringing the latest non-invasive archaeological investigation methods.